2009
DOI: 10.4076/1757-1626-2-6282
|View full text |Cite
|
Sign up to set email alerts
|

Delayed post-operative contralateral epidural hematoma in a patient with right-sided acute subdural hematoma: a case report

Abstract: Head injury is one of the leading causes of death and disability in traumatic accidents. Post-operative contralateral epidural hematomas after surgery for acute subdural hematoma seem to be rare. In this case, expansion and spontaneous resolution of a fractural epidural hematoma contralateral to the side of acute subdural hematoma is presented. The importance of immediate post-operative computed tomography is also highlighted to detect delayed traumatic mass lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 11 publications
0
31
1
5
Order By: Relevance
“…Moreover, the development of a contralateral hematoma at the evacuation site of an acute SDH or EDH is also rare 7). Authors have reported various incidence rates (very rare to 5.7%) of contralateral hematoma after evacuating an ipsilateral hematoma 2681014). In our study, the initial diagnoses of the patients were six (50%) SDH, four (33.3%) EDH, and two (16.7%) CH.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Moreover, the development of a contralateral hematoma at the evacuation site of an acute SDH or EDH is also rare 7). Authors have reported various incidence rates (very rare to 5.7%) of contralateral hematoma after evacuating an ipsilateral hematoma 2681014). In our study, the initial diagnoses of the patients were six (50%) SDH, four (33.3%) EDH, and two (16.7%) CH.…”
Section: Discussionmentioning
confidence: 55%
“…However, many neurosurgeons have experienced such cases. Several neurosurgical procedures are associated with the incidence of contralateral hematoma, including evacuating an acute or chronic SDH and inserting a ventriculo-peritoneal shunt 10). Moreover, the development of a contralateral hematoma at the evacuation site of an acute SDH or EDH is also rare 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cases included 81% contralateral skull fractures and 76% intraoperative acute brain swelling. 28 Our patient was male, 19 years old and had contralateral skull fractures.…”
Section: Discussionmentioning
confidence: 89%
“…EDH is extremely rare, with only 38 cases after decompressive craniectomy presented in the literature. [25][26][27][28][29][30] Panourias et al, Matsuno et al, and Meguins et al reported contralateral epidural hematoma after decompressive craniectomy for acute subdural hematoma. 5,31,32 Shen et al evaluated published data via Pubmed and found a rate of 2.4% for contralateral EDH after acute subdural hematoma.…”
Section: Discussionmentioning
confidence: 99%